(Non-)Sharing as a Form of Maternal Care? The Ambiguous Meanings of Sharenting for Mothers of 0- To-8-Year-Old Children - Mascheroni, Giovanna; Cino, Davide; Amadori, Gaia; Zaffaroni, Lorenzo Giuseppe (Italian Sociological Review, 2023)
The present article reports on findings from a survey administered in (country anonymised) to a national representative sample of parents of children aged 0-8 around their sharenting behaviour. We first frame sharenting as a complex phenomenon where gendered, generational and agentic matters intertwine and mingle in complex ways. We then report results from a cluster analysis aimed at identifying different sharenting styles reflecting the scale and scope of parents’ sharing behaviour among our sample. The relationships between sharenting styles and parents’ socio-demographics, as well as parental practices of privacy management are further explored and reported. Altogether, findings provide insights into the experience of sharenting in family life pointing to a variety of sharing practices, while also showing first that sharenting represents a key site of identity performance for young mothers, and then how parents negotiate and manage related issues of agency and privacy.